Locating large insects using automated VHF radio telemetry with a multi‐antennae array. Issue 3 (11th December 2020) - Fisher, Kelsey Elizabeth; Dixon, Phil M.; Han, Gang; Adelman, James Stephen; Bradbury, Steven P.
Abstract: We describe an automated radio telemetry system (ARTS) designed for estimating the location of 0.50 g butterflies which was constructed with commercially available materials. Previously described systems were not designed to estimate fine‐scale locations of large insects within approximately 200 m 2 study areas. The ARTS consists of four receiving stations. Each receiving station has four 3‐element, directional Yagi antennae (separated by 60) connected to an automated receiver that records detected power sequentially from each antenna. To develop and evaluate the ARTS performance, four receiving stations were installed in the corners of 4 and 6.25‐ha square fields with varying heights of vegetative cover. The location of a 0.22 g transmitter was estimated with a statistical method implementing both distance‐and angle‐power relationships. Calibrated model parameters were based on power detected from transmitters at known locations. Using independently collected data, model performance was evaluated based on estimated locations of a georeferenced stationary transmitter, a moving transmitter with a known georeferenced path and a transmitter attached to a monarch butterfly Danaus plexippus . Estimated locations were calculated as frequently as every 5 s, which is at least 12 times greater than the sampling frequency previously reported for tracking insects. When sufficient power data were received, the median estimated locations of a transmitter attached to an investigator's hat were <16 m from the true location. The median effective radius of the 95% confidence ellipse was 18.3 m for stationary targets and 15.9 m for a moving transmitter. Greater error in location estimation was expected when the transmitter was attached to a monarch butterfly due to interference from vegetation and variability in antenna orientation and transmitter height. As such, the median distance between the estimated and true locations was 72 m. After applying a correction for the effect of vegetation, median location error was reduced by 12 m. While our ARTS has likely reached the limit of current technology, the system is still a substantial methodological advancement for locating butterflies. Our efforts should provide a benchmark as technology improves.